Durham university: last of the ancient universities and first of the new (1831-1871) - Andrews, M (2016)
This thesis is a study of Durham University, from its inception in 1831 to the opening of the College of Physical Science in Newcastle in 1871. It considers the foundation and early years of the University in the light of local and national developments, including movements for reform in the church and higher education. The approach is holistic, with the thesis based on extensive use of archival sources, parliamentary reports, local and national newspapers, and other primary printed sources as well as a newly-created and entirely unique database of Durham students. The argument advanced in this thesis is that the desire of the Durham authorities was to establish a modern university that would be useful to northern interests, and that their clear failure to achieve this reflected the general issues of the developing higher education sector at least as much as it did internal mismanagement. This places Durham in a different position relative to the traditional understanding of how universities and colleges developed in England and therefore broadens and deepens the quality of that narrative. In the light of the University's swift decline, and poor reputation, from the mid-1850s what were the ambitions of the founders and how did this deterioration occur? Were the critics' accusations against the University – principally that it was a theologically-dominated, inadequate imitation of Oxford, bound to the Chapter of Durham and ruled autocratically by its Warden – based on fact or prejudice? And if the critics were wrong, what were the factors that lead to the University’s failings?